Application of Information Technology in Administrative Services at the Population and Civil Registration Office of Badung Regency - Pramesti, Ni Putu Dinda Puspa; Wirantari, I Dewa Ayu Putri (West Science Business and Management, 2025)
The application of information technology in population administration services is one of the strategic efforts to improve the quality, efficiency, and effectiveness of public services. This study aims to examine the implementation of information technology at the Population and Civil Registration Office of Badung Regency, especially in the use of the online application "Aku Dicari" and other digital systems that support the acceleration of the processing of population documents such as electronic ID cards, family cards, and civil registration certificates. The research method used is a descriptive study with a qualitative approach, including interviews, observations, and document analysis. The results of the study show that the application of information technology has had a positive impact in the form of accelerating administrative processes, increasing service accessibility, and increasing public satisfaction, especially during the Covid-19 pandemic. However, challenges such as the limitations of technology infrastructure and people's digital literacy still need attention. This study recommends strengthening human resources and intensive socialization so that information technology innovations in population administration can run optimally. Thus, the application of information technology in the Badung Regency Disdukcapil can become a modern, responsive, and community-oriented public service model.